2005
DOI: 10.1093/hmg/ddi134
|View full text |Cite
|
Sign up to set email alerts
|

The Parkinson's disease-associated DJ-1 protein is a transcriptional co-activator that protects against neuronal apoptosis

Abstract: Mutations in the DJ-1 gene cause early-onset autosomal recessive Parkinson's disease (PD), although the role of DJ-1 in the degeneration of dopaminergic neurons is unresolved. Here we show that the major interacting-proteins with DJ-1 in dopaminergic neuronal cells are the nuclear proteins p54nrb and pyrimidine tract-binding protein-associated splicing factor (PSF), two multifunctional regulators of transcription and RNA metabolism. PD-associated DJ-1 mutants exhibit decreased nuclear distribution and increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
195
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 38 publications
6
195
1
Order By: Relevance
“…Deletion and point mutations of DJ-1 have been shown to be responsible for onset of familial Parkinson's disease, PARK7 [5]. DJ-1 is a multi-functional protein and plays roles in transcriptional regulation [8][9][10][11][12][13][14][15] and in modulation of signaling cascades [16][17][18][19][20] through protein-protein interaction, leading to anti-oxidative stress function [21][22][23]. Furthermore, we have reported that DJ-1 activated TH and DDC through direct binding to TH and DDC in an oxidative status of DJ-1-dependent manner [24] and that human DJ-1 activates TH gene expression in cultured human dopaminergic cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…Deletion and point mutations of DJ-1 have been shown to be responsible for onset of familial Parkinson's disease, PARK7 [5]. DJ-1 is a multi-functional protein and plays roles in transcriptional regulation [8][9][10][11][12][13][14][15] and in modulation of signaling cascades [16][17][18][19][20] through protein-protein interaction, leading to anti-oxidative stress function [21][22][23]. Furthermore, we have reported that DJ-1 activated TH and DDC through direct binding to TH and DDC in an oxidative status of DJ-1-dependent manner [24] and that human DJ-1 activates TH gene expression in cultured human dopaminergic cells [15].…”
Section: Introductionmentioning
confidence: 99%
“…DJ-1 also functions as a transrepressor of a key tumor suppressor, PTEN (phosphatase and tensin homolog on chromosome 10), to regulate c-Myc and the catalytic unit of the telomerase complex, human telomerase reverse transcriptase (Sitaram et al, 2009). It contributes to cell survival by interacting with p54nrb to inhibit the silencing activity of pyrimidine tract-binding protein-associated splicing factor (Xu et al, 2005) or by regulating androgen receptor transcriptional activity (Takahashi et al, 2001;Niki et al, 2003;Tillman et al, 2007). Recently, DJ-1 was found to repress p53 (Bretaud et al, 2007;Fan et al, 2008a, b;Giaime et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…DJ-1 is conserved in bacteria, plants, animals, and humans (Lucas and Marin, 2007). It is well known that DJ-1 has multiple functions including anti-oxidant and chaperone functions associated with PD pathogenesis (Menzies et al, 2005;Xu et al, 2005;Zhou et al, 2006). However, DJ-1 deficiency or loss-of-function leads to oxidative stressinduced cell death in vitro and in vivo (Chen et al, 2005;Goldberg et al, 2005;Kim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have demonstrated that DJ-1 protein protects against neuronal cell death resulting from 6-OHDA-induced ROS. After exposure to dopaminergic neurotoxins including rotenone and 6-OHDA, intracellular ROS levels were inversely correlated with DJ-1 expression levels, suggesting that DJ-1 may mitigate 6-OHDA-induced oxidative stress and help protect cells against oxidative stress (Menzies et al, 2005;Xu et al, 2005;Zhou et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation